Speed Control of Direct Current Motor via Pole Placement Control (University of Khartoum Engineering Journal, 2022)
This paper describes a separately excited DC motor speed control using armature voltage control method, based on traditional Proportional- Integral- Derivative (PID) controller, and pole assignment, feedback control technique. The main objective of the proposed controller is to control the speed of a DC motor shaft rotation and overcome problems like overshoot, and increasing the system model order, that are caused by PID controller, with a step response. Results obtained with Ziegler – Nichols PID controller were compared with those obtained using pole placement. DC motor response contains a 24% overshoot with PID controller; compared with 0.0286% overshoot. In the response of pole placement controller, it is found that pole placement reduces system overshoot to 0.0015% ofthe closed loop system.